(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
India is a vast country with large population and diverse needs, present a huge challenge in the retail sector for market researchers, in terms of the need of innovation, new business practices, new products and technology. Retail industry is fast growing with increasing outlets and chain stores within the addition of shopping malls and large departmental stores, super markets and multi brand outlets. However, this sector faces many challenges and traditional retailing is expecting a tough time ahead within the emergence of E-shopping or on-line shopping. E-shopping most obvious edge is in selection and convenience. Even the biggest departmental store cannot store as many items that companies like Amazon can offer. E-retailers are also competing as new kind of service and pricing. Online, a shopper can easily compare prices between differently retailers instead of visiting retailers, as in traditional shopping, thus saving precious time and money. In this paper we study about the research done in the field of E-Marketing